Difluoromethylation and gem-difluorocyclopropenation with difluorocarbene generated by decarboxylation1. Issue 42 (25th May 2015) - Deng, Xiao-Yun; Lin, Jin-Hong; Zheng, Jian; Xiao, Ji-Chang
<x xml:space="preserve">Abstract</x> Difluoromethylation of the activated X–H bond and aliphatic thiols, and gem-difluorocyclopropenation of alkynes with difluorocarbene generated by decarboxylation are described.